2013
DOI: 10.1016/j.matlet.2012.10.118
|View full text |Cite
|
Sign up to set email alerts
|

Towards a mechanistic model for the interaction between plastically deforming particles under confined conditions: A numerical and analytical analysis

Abstract: Triaxial compression of plastically deforming particles was studied with the finite element method in order to identify the mechanisms that underlie their mechanical response under confined conditions. In addition to the established elastoplastic behaviour at small and intermediate strains, the coalescence of plastic zones centred at contacts resulted in a reduced stiffness, whereas a significantly increased stiffness was seen once the material displaced by plastic deformation filled the ambient void space, si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(48 citation statements)
references
References 14 publications
3
45
0
Order By: Relevance
“…A FEM model developed and described by Frenning [11] for confined compression of single particles was used for comparison with the experimental results from the compression of CA particles. For this simulation, parameters corresponding to spherical particles with a diameter of 2 mm were used.…”
Section: Comparison With Contact Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…A FEM model developed and described by Frenning [11] for confined compression of single particles was used for comparison with the experimental results from the compression of CA particles. For this simulation, parameters corresponding to spherical particles with a diameter of 2 mm were used.…”
Section: Comparison With Contact Modelsmentioning
confidence: 99%
“…However, under uniaxial particle compression, there are two such contacts acting on the same particle. Even though these contacts do not impinge, the propagation of plastic deformation tend to lead to coalescence of plastically deformed zones at higher strains (see for example [11]), thus affecting the contact forces. Compared to the triaxial curves, the AF model assumes full plasticity and contact independence and hence becomes invalid in modelling triaxial compression at strain levels where contact impingement becomes significant, which also can be seen in Figure 10.…”
Section: The Ability Of the Apparatus To Compress Under Confined Condmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparison with FEM/DEM results indicated that a superior representation of the particle responses under compression was obtained when contact dependence was properly accounted for. As a first step towards a mechanistic model for the interaction between plastically deforming particles under confined conditions, a geometrical analysis of the deformed particle shape was made in terms of a truncated sphere whose radius increased to accommodate the displaced material [19], building on the work by Fischmeister and Arzt [2] and Montes et al [20].…”
Section: Introductionmentioning
confidence: 99%
“…Later, Hanley et al [15] explained the failure of agglomerates at compressive loading using intricate numerical simulations of primary particles. The valuable work of Frenning [16] comparing the material behavior of different granules at different modes of compression using advanced simulation techniques has provided exceptional qualitative information regarding the simulation of particle behavior at compression. Several other researchers have also contributed to the existing knowledge of the material behavior of different types of granular materials and agglomerates under cyclic loading conditions.…”
Section: Introductionmentioning
confidence: 99%